REFORMULASI TERKAIT DENGAN PASAL 2 UNDANG-UNDANG NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG DALAM PEMBAHARUAN HUKUM POSITIF DI INDONESIA - Vira Andina Putri; Mukhlis R; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In Article 2 of Law Number 21 of 2007 concerning the Eradication of theCrime of Trafficking in Persons, it contains a minimum criminal sanction of 3(three) years which is deemed not to fulfill a sense of justice considering thatvictims experience violence which has an impact on the physical and psychologicalas well as morals of victims, moreover the majority victims are women and childrenwho incidentally are weak people. Therefore, as an effort to combat trafficking inpersons which is increasing and the importance of giving birth to a formulationthat is in accordance with the needs of the community, it is necessary to carry outreformulations related to criminal sanctions for trafficking in persons which arecontained in Article 2 Paragraph 1 Law Number 21 of 2007 concerningEradication of the Crime of Trafficking in Persons to present a law that is moreappropriate in responding to the modernization needs of society. The purpose ofthis research was to find out the arrangements and application of criminalsanctions for the Crime of Trafficking in Persons in the Indonesian legal system, aswell as forming ideas reformulation of appropriate sanctions against the Crime ofTrafficking in Persons.This research method is normative legal research. It is also called doctrinallegal research, namely legal research that uses data from literature that is relatedto the problem under study. Thus this study uses secondary data sources consistingof primary, secondary, and tertiary legal materials.From the results of the research conducted, several conclusions can bedrawn, namely, First, the perspective of the judge in imposing criminal sanctionsconsiders 2 (two) factors. Second, the ideal sanction in the crime of trafficking inpersons is to increase criminal sanctions in the form of imprisonment and finesaccording to how much influence the perpetrator has over this crime.Keywords: Reformulation – Criminal Sanctios – Trafficking in Persons